2017
DOI: 10.21577/0100-4042.20170148
|View full text |Cite
|
Sign up to set email alerts
|

Esterificação E Transesterificação Homogênea De Óleos Vegetais Contendo Alto Teor De Ácidos Graxos Livres

Abstract: HOMOGENEOUS ESTERIFICATION AND TRANSESTERIFICATION OF VEGETABLE OILS WITH HIGH FREE FATTYACIDS CONTENT. The high free fatty acids content in some vegetable oils can have a negative impact in the sustainable production of biodiesel. The previous treatment of these feedstock oils can contribute to the reduction of the process total costs as well as the environment, turning the biodiesel a more competitive in relation to the fossil diesel. The aim of this work was to adequate low cost vegetable oils to the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
0
21
0
8
Order By: Relevance
“…It is further suggested that coconut oil and cacay butter had a high free fatty acid concentration formed by a hydrolytic rancidity process at the time of analysis. Artisanal oils are usually obtained by mechanical extraction, and are more susceptible to chemical degradation due to thermal processing and light exposure [31,32].…”
Section: Plos Onementioning
confidence: 99%
“…It is further suggested that coconut oil and cacay butter had a high free fatty acid concentration formed by a hydrolytic rancidity process at the time of analysis. Artisanal oils are usually obtained by mechanical extraction, and are more susceptible to chemical degradation due to thermal processing and light exposure [31,32].…”
Section: Plos Onementioning
confidence: 99%
“…Inicialmente, realizou-se a pesagem do metanol (CH 3 OH), do hidróxido de sódio (NaOH) e do óleo. Essa metodologia foi empregada em razão do afirmado por Vieira et al (2018), que apontam a transesterificação como o método mais utilizado nas indústrias para a produção de biodiesel quando se deseja usar catalisador alcalino. Tebas et al (2017) explicam que os principais reagentes que fornecem melhores resultados para conversão são o álcool metílico e o catalisador alcalino.…”
Section: Produção Do Biodieselunclassified
“…According to Taketa et al (2013), transesterification, shown in Figure 1, consists of a reaction between triglyceride and alcohol, resulting in a new ester and glycerol (MENEGHET-TI; MENEGHETTI; BRITO, 2013). Transesterification is the most common method for biodiesel production in industries when using an alkaline catalyst due to some advantages, such as higher yield, being more selective and less corrosive, its low cost, and the lower amount of catalyst required (VIEIRA et al, 2018;GERIS et al, 2007). The main reagents with better conversion results are methyl alcohol, soybean oil, and alkaline catalyst (TEBAS et al, 2017).…”
Section: Transesterification Reactionmentioning
confidence: 99%